A novel model of human lympho-myeloid progenitor hierarchy based on single cell functional and transcriptional analysis - Karamitros, D; Stoilova, B; Aboukhalil, Z; Reinisch, A; Hamey, F; Samitsch, M; Quek, L; Otto, G; Repapi, E; Doondeea, J; Usukhbayar, B; Calvo, J; et al. (Ferrata Storti Foundation, 2017)
Human hemopoiesis produces 10 billion new, terminally mature, blood cells daily; a production that is also rapidly responsive to external change. Dysregulation of this complex process can lead to hemopoietic and immune deficiencies and blood cancers. In humans the hemopoietic progenitor hierarchy producing lymphoid and granulocytic-monocytic (myeloid) lineages is unclear. Multiple progenitor populations give rise to lymphoid and myeloid cells but they remain incompletely characterized at the immunophenotypic, transcriptional and functional level.